Evaluation Of The Process Of Implementing Pjok Learning In Agribusiness SMK In Bengkulu City Using The Cipp Model - Beli Saputra Irawan; Ajis Sumantri; Feby Elra Perdima (Sinar Sport Journal, 2023)
This study aims to evaluate the learning process of physical education in SMK Agribusiness Bengkulu City, which includes: (1) Context: the relevance of physical education learning materials with KTSP; (2) Input: teacher background and physical education facilities and infrastructure; (3) Process: implementation of physical education learning; and (4) Product: Students' learning achievement. This research method is an evaluation research using the CIPP (Context, Input, Process, Product) model developed by Stufflebeam (1985) using a qualitative descriptive approach. The research subjects included 1 physical education teacher and 75 students. This research was conducted at SMK Agribusiness Bengkulu City. Data collection was done by documentation, observation, and interview. Qualitative data were analyzed with descriptive techniques. The validity of the research instrument was carried out using excel. The results showed:(1) based on the results of the Context evaluation, the learning materials used are relevant to KTSP, but there are several policies from teachers related to school limitations; (2) the results of the input evaluation show that the teaching teacher's educational background is Bachelor of Education (S1) majoring in Sports Education with 4 years of teaching experience, while the suitability of PE facilities and infrastructure shows a level of suitability of 69.23% including the good category; (3) the results of the process evaluation which includes the implementation of physical education learning in the good category; (4) product evaluation, namely student learning achievement in the good category.